Exploring Challenges and Strategies of Non-Native English Speaking Teachers (NNESTs) in Teaching Using Authentic Materials - Gustam, Ririn Fadilah (Universitas Pendidikan Indonesia (UPI), 2025)
This study explores the challenges and strategies of Non-Native English-Speaking Teachers (NNESTs) in utilizing authentic materials for teaching speaking in a non-formal educational setting in Indonesia. Using a qualitative case study approach, data were collected through classroom observations and semi-structured interviews with one NNEST and students at varying proficiency levels. Thematic analysis revealed several prominent challenges, including mixed-level classrooms, technical limitations, and the ideological pressure of native-speakerism. These challenges were particularly evident in the use of digital authentic materials, which were disrupted by power outages and limited resources. Despite these constraints, NNEST demonstrated pedagogical resilience by employing flexible teaching strategies such as using whiteboards, printed realia, games, and emotional engagement techniques to foster students’ motivation. Additionally, the teacher implemented a learner-centered approach by conducting placement tests, tailoring materials to students’ needs, and prioritizing intelligibility over native-like pronunciation. Students responded positively to these strategies, noting that the use of authentic materials and engaging classroom activities improved their speaking confidence and made learning more enjoyable. The findings highlight the importance of adaptability, cultural awareness, and strategic planning in enhancing speaking instruction through authentic materials. This research adds to the literature on NNESTs and provides insights for EFL teaching.